Crecimiento del caimán del Orinoco (Crocodylus intermedius, Crocodylia: Crocodylidae) en dos condiciones de cautiverio - T. Pérez T., Aldeima (2008)
In order to determine the growth of Caiman of the Orinoco (Crocodylus intermedius) under two conditions of captivity, 40 specimens were raised during 11 months and 15 days in two circular tanks, with 28.3 m2 of surface area and a volume of 62.2 m3 in each tank. The tanks were built with concrete walls and guarded blocks covered internally with sheets of myrrhlike resin, and a roof of galvanized sheets. One tank was covered partially with the galvanized sheets (tank I), the other was totally covered (tank II). Twenty caimans were placed in each tank, and both groups were fed with 85% beef, 10% fresh fish, 5% hen eggs and a mixture of minerals and vitamins. The length and weight differed significantly between the groups (p < 0.001). Mean growth (103.0 ± 6.81 cm) and weight (3 987 ± 0.98 g) were higher in tank II, (tank I: 88.9 ± 7.58 cm; 2 705 ± 0.69 g). The greater growth in tank II reflects higher air and water temperatures. The survival rate was 97.5%. These results can be used for rearing caimans in captivity for conservation and commercial purposes.